Douglas H. Pratt letter to Nicholas S. Halmi regarding bird sightings, November 21, 1978 - Pratt, H. Douglas (Harold Douglas), 1944-et al (1978)
Letter from Douglas H. Pratt to Nicholas S. Halmi regarding bird sightings, November 21, 1978. Some of the sightings were made by Gary Wee. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly Field Report of fall 1978. Epson - sheet feed/flatbed